Digital literature and critical theory - Elstermann, Annika (Taylor & Francis Group, 2022)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Acknowledgements -- Introduction -- 1 Core Examples -- 2 Partitioned Works and Seriality -- 3 Participatory Storytelling -- 4 Interactive Text Production -- 5 Computer-Generated Text -- 6 Conclusion -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift